Identifying hubs and spokes in global supply chains using redirected trade in value added - Arjan Lejour; Hugo Rojas-Romagosa; Paul Veenendaal (European Central Bank (ECB), 2014)
The increasing importance of global supply chains has prompted the use of analytical tools based on trade in value added – instead of traditional measures in gross value. We use this analytical framework to develop indicators that identify hubs and spokes in international supply chains. Using these indicators and the Global Trade Analysis Project (GTAP) databases we identify the importance of redirected value added trade and the hub and spoke relationships at the aggregate level and for specific highly integrated industries.
Keywords: F1; C67; D57; 330; global input-output tables; global supply chains; hubs and spokes; Trade in value added; Vertical specialization